Development of Student Worksheets (LKPD) Based on Higher Order Thinking Skill (HOTS) On Two Variable Linear Equation Systems (SPLDV) - Halimah, Nur (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2022)
The purpose of this study was to determine the validity and feasibility of the LKPD and to determine student responses to the HOTS-based LKPD that was developed. This study uses the Research and Development (RnD) method with the ADDIE model. The model consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The data collection technique used a questionnaire in the form of a Likert scale to determine the validity and feasibility as well as student responses to the developed Student Worksheet (LKPD). The results of the research are the Development of Student Worksheets (LKPD) Based on Higher Order Thinking Skills (HOTS) on the Material of the Two Variable Linear Equation System (SPLDV) which are valid and suitable for use and excellent student responses to the HOTS-based LKPD. Based on the results of media expert validation, a percentage score of 80% was obtained in the